PELATIHAN MASYARAKAT TENTANG PENANGANAN TUBERKULOSIS DENGAN KOMPLIKASI DIABETES MELLITUS DALAM MASA PANDEMI COVID-19 - Lalangpuling, I.E.; Konoralma, K.; Rambi, E.V.; Sumampouw, J.E. (Buletin Udayana Mengabdi; Vol 22 No 1 (2023): Buletin Udayana MengabdiDO - 10.24843/BUM.2023.v22.i01.p08, 2023)
Diabetes Mellitus (DM) is a metabolic disorder in which blood sugar levels exceed normal levels. and if people with type 2 DM do not undergo regular treatment, they have the opportunity to suffer from tuberculosis as a DM comorbidity. The purpose of this training is to empower the community to participate in the management and prevention of complications of DM in Sea Dua Village, Pineleng District, Kabupaten Minahasa by providing health education. Before Health Education intervention, a pre-test was given to participants to measure initial behavior about TB DM, after that Health Education was carried out in the form of counseling on TB-DM material, and the last training a post-test was to be done. Blood sugar screening was also carried out to determine the participants' blood sugar levels. Result of this activity is good therefore partisipants gave good respons. So that recommended that this activity be carried out in the future with more participants. To disseminate Health Education to the general public about handling, controlling and preventing TB complications. Keywords: Training, Community, Tuberculosis, DM Complication